Common and unusual CT and MRI manifestations of pancreatic adenocarcinoma: a pictorial review - Yang, Min-Jie; Li, Su; Liu, Yong-Guang; Jiao, Na; Gong, Jing-Shan (Quantitative Imaging in Medicine and Surgery, 2013)
Pancreatic adenocarcinoma is the most common malignancy of the pancreas with high death rate. Preoperative imaging is crucial for the assessment of the disease and the planning of treatment. In this review, we discussed the common and unusual findings of pancreatic carcinoma. The common CT and MR findings include hypovascular mass, dilataion of upstream biliary and pancreatic ducts, invasion to adjacent structures and metastasis. The uncommon CT and MR findings include: a cystic mass, a mass without dilataion of upstream ducts, multiple masses or a lesion diffusively infiltrating most parts of the pancreas without distorting its configuration.